Rethoric and Discourse Studies - Teixeira, Lucia (2015)
This article aims to discuss the articulation between rhetoric and discourse, basing its reflections on José Luiz Fiorin’s Figuras de retórica [Figures of Rhetoric] (2014). This work examines the contribution of Classical Rhetoric to Discourse Studies. It retrieves and brings a new meaning to the idea of ornament, which relegated Rhetoric to a mere study of images/figures. It presents figures as enunciative operations that intensify the meaning of some elements of discourse, restituting them with their argumentative dimension. The article incorporates, into its own argumentation, the figures of speech and rhetorical resources that are explained by the author of the book.